The analysis of theoretical and methodological foundations of pedagogical conception of culture protection by V. Schepotiev (1880–1937) - Hryn', Yuliya; Lobach, Olena (ScienceRise: Pedagogical Education, 2017)
The article analyzes the theoretical-methodological foundations of pedagogical conception of culture protection by V. Schepotiev – first rector of Poltava institute of national education, professor, ethnographist, archivist, artist, sentenced in the matter of Ukrainian Liberation Union and executed in 1937 year. There were elucidated in details the purposeful, methodological and theoretical concepts of scientist’s pedagogical conception, namely: – Purposeful one includes the purpose of education – the formation of national consciousness in young generation by the means of Ukrainian culture, the formation of responsibility for it to the succession, training of pupil youth to the activity in culture protection; – Methodological concept is grounded on the following statements: human is a child of culture; the separate cultures interact, influence each other and form integrity; national culture is an inalienable component of general human one; in national culture the most importance belongs to language, folklore and art as the expression of individual worldview of nation and “public moods” in concrete historical epoch; each generation must save culture to the succession; – Theoretical one includes: 1) general pedagogical and specific principles, especially nationality, culture-correspondence, democratism, humanism, emotionality; 2) pedagogical conditions: the understanding of culture protective and culture creating mission by scientific-pedagogical intellectuals; the widening of net of culture protective state institutions and public organizations; interconnection between family, secondary and higher schools, out-of-school institutions, church and public organizations in culture protective activity; introduction of culturological approach to the system of education